Dental Services and Health Outcomes in the New York State Medicaid Program. (August 2021) - Lamster, I.B.; Malloy, K.P.; DiMura, P.M.; Cheng, B.; Wagner, V.L.; Matson, J.; Proj, A.; Xi, Y.; Abel, S.N.; Alfano, M.C.
Previous reports suggest that periodontal treatment is associated with improved health care outcomes and reduced costs. Using data from the New York State Medicaid program, rates of emergency department (ED) use and inpatient admissions (IPs), as well as costs for ED, IPs, pharmacy, and total health care, were studied to determine the association of preventive dental care to health care outcomes. Utilization of dental services in the first 2 y (July 2012–June 2014) was compared to health care outcomes in the final year (July 2014–June 2015). Costs and utilization for members who did not receive dental services (No Dental) were compared to those who received any dental care (Any Dental), any preventive dental care (PDC), PDC without an extraction and/or endodontic treatment (PDC without Ext/Endo), PDC with an Ext/Endo (PDC with Ext/Endo), or Ext/Endo without PDC (Ext/Endo without PDC). Propensity scores were used to adjust for potential confounders. After adjustment, ED rate ratios were significantly lower for PDC and PDC without Ext/Endo but higher for the Any Dental and Ext/Endo without PDC. IP ratios were lower for all treatment groups except Ext/Endo without PDC. ED costs differed little compared to the No Dental group except for Ext/Endo without PDC. For IPs, costs per member were significantly lower for all groups (−$262.91 [95% confidence interval (CI), −325.40 to −200.42] to −$379.82 [95% CI, −451.27 to −308.37]) except for Ext/Endo without PDC. For total health care costs, Ext/Endo without PDC had a significantly greater total health care cost ($530.50 [95% CI, 156.99–904.01]). Each additional PDC visit was associated with a 3% reduction in the relative risk for ED and 9% reduction for IPs. Costs also decreased for total health care (−$235.64 [95% CI, −299.95 to −171.33]) and IP (−$181.39 [95% CI, −208.73 to −154.05]). In conclusion, an association between PDC and improved health care outcomes was observed, with the opposite association for Ext/Endo without PDC.